2002
DOI: 10.17221/4361-pse
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of cyclamen (Cyclamen persicum) and poinsettia (Euphorbia pulcherrima) with arbuscular mycorrhizal fungi and Trichoderma harzianum

Abstract: Dual inoculation of peat based horticulture substrate with a mixture of four species of arbuscular mycorrhizal fungi and fungal biocontrol agent Trichoderma harzianum showed a significant positive effect on the growth and flowering of cyclamen plants. Inoculation substantially decreased plant mortality caused by spontaneous infection by the fungal pathogen Cryptocline cyclaminis. Plant mortality was also reduced by separate inoculation with arbuscular mycorrhizal fungi. Both separately inoculated agents positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
6
1
Order By: Relevance
“…It was reported that shoot length, leaf number, and shoot dry weight were increased in P. emblica inoculated with G. fasciculatum, S. dussi, and A. laevis [26] and in Senna spectabilis (Fabaceae) inoculated with G. etunicatum and Glomus macrocarpum [28]. In contrast to our results, inoculation with a mixture of Glomus claroideum, G. mosseae, G. intraradices, and G. geosporum did not increase plant height, stem dry weight, and leaf dry weight of Euphorbia pulcherrima due to the late inoculation and poor colonization (34%) [29]. Similarly, poor colonization by commercial AM fungi (0.17%) did not increase plant height, collar root diameter, and biomass production of A. saman 30-170 days after transplanting [30].…”
Section: Discussioncontrasting
confidence: 99%
“…It was reported that shoot length, leaf number, and shoot dry weight were increased in P. emblica inoculated with G. fasciculatum, S. dussi, and A. laevis [26] and in Senna spectabilis (Fabaceae) inoculated with G. etunicatum and Glomus macrocarpum [28]. In contrast to our results, inoculation with a mixture of Glomus claroideum, G. mosseae, G. intraradices, and G. geosporum did not increase plant height, stem dry weight, and leaf dry weight of Euphorbia pulcherrima due to the late inoculation and poor colonization (34%) [29]. Similarly, poor colonization by commercial AM fungi (0.17%) did not increase plant height, collar root diameter, and biomass production of A. saman 30-170 days after transplanting [30].…”
Section: Discussioncontrasting
confidence: 99%
“…Observed significant (P < 0.05) growth due to mycorrhizal infection in tomatoes confirms other reports that AMF symbiosis with host plant has an improved growth effect (10,22). Increased growth due to mycorrhizal infection is mainly attributed to improved phosphorous and micronutrient uptake in the host plant (13,20).…”
Section: Effect Of Treatments On Growth and Wilt Pathogen Controlsupporting
confidence: 89%
“…Inoculation with AM fungi at very early stages has been found to result in higher crop uniformity, reduce transplant mortality (Waterer and Coltman 1988) and higher yields after transplanting to the field (Lovato et al 1996;Vosalka 1995). Since in most soils the indigenous population of AM fungi/bioinoculants are present, the pre-inoculation of cuttings in sterilized substrates in nurseries, provides the introduced bacterial/ fungal strains a special advantage over the indigenous bacterial/fungal strains after transplanting in field (Dubsky et al 2002;Sorensen et al 2008). Bierman and Linderman (1983) reported that even low levels of root colonization (\10%) spread rapidly to new roots after transplanting which might be adequate for successful establishment of mycorrhizal plants after transplanting; a colonization of 18-21% was observed in nursery in the present study.…”
Section: Discussionmentioning
confidence: 99%